1987
DOI: 10.1007/bf01244102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term lithium administration on tryptophan levels and 5-hydroxytryptamine synthesis in whole brain and brain regions in rats

Abstract: The effects of short-term lithium administration on tryptophan levels and 5-hydroxytryptamine (5-HT) synthesis in whole brain and brain regions in rats were studied. Short-term lithium administration was found to increase whole brain tryptophan levels without affecting whole brain 5-HT synthesis. However, the increase of tryptophan varied between various brain regions, which may possibly be due to differences in the synaptosomal uptake of tryptophan between brain regions. In the striatum, where the tryptophan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Swann et al [16], Berggren [2] and Herrero et al [8] have shown that lithium increases the transport of tryptophan into the brain, thereby increasing its concentration in the serotoninergic endings and inducing the synthesis of serotonin released into the synaptic cleft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Swann et al [16], Berggren [2] and Herrero et al [8] have shown that lithium increases the transport of tryptophan into the brain, thereby increasing its concentration in the serotoninergic endings and inducing the synthesis of serotonin released into the synaptic cleft.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is thought to be brought about by lithium bringing about an increase in the tryptophane uptake inside the brain and inducing an increase in serotonin synthesis within the brain's neurons [2,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation